Active protease formulation in commodity polymers withstands melt processing into compounds and blown films. (March 2023) - Böhler, Stefan; Rosencrantz, Sophia; Wolf, Karina; Heinemann, Robert; Schmidt, Peer; Ganster, Johannes; Büsse, Thomas; Balko, Jens; Rosencrantz, Ruben R.
Abstract: Integrating enzymes into thermoplastic polymers is challenging due to their lack of robustness with respect to temperature and shear fields during conventional melt processing. In the present study, blown films from low-density polyethylene (LDPE) were prepared containing a technical protease from Bacillus sp . First, LDPE/protease compounds were produced followed by blown film extrusion, both processes at melt mass temperatures of 130 °C or higher. Enzyme activity was proven, both for the LDPE/protease compound and the blown film. The highest enzyme activity in the compound was determined for processing at 132 °C and a screw speed of 75 rpm. The influence of melt temperature and shear fields was studied in detail. Enzyme activities were determined for melt temperatures up to 160 °C and for screw speeds ranging from 75 to 300 rpm during compounding by twin-screw extrusion. The process was also applied for biobased and biodegradable polyesters, where similar protease activity after compounding was verified. Electron microscopy, X-ray diffraction, nuclear magnetic resonance spectroscopy and differential scanning calorimetry served to analyze components and morphology of the enzyme formulation used here. It is proposed that the porous morphology of the protease particles is beneficial for the enzyme to remain active after processing. Additionally, the polymer matrix surrounding the particles protects the protease at elevated temperatures, which can be attributed to thermal insulation. Thus, the right combination of a suited technical enzyme formulation with appropriate mild melt compounding conditions allows enzymes to be incorporated into thermoplastics and retain their activity. This opens the way to use the abundant biological functions of enzymes in thermoplastic applications. Graphical Abstract: ga1